la violencia intrafamiliar y protección de derechos en la unidad judicial violencia contra la mujer y la familia, machala 2023 - Robles Illescas, Josselyn Edith; Honores Sanmartin, Adriana Lissbeth (Machala: Universidad Tecnica de Machala, 2024)
The research responds to the violation of women's rights due to domestic violence with evidence in cases registered in the Judicial Unit of Violence against Women and the Family in the city of Machala and based on what has been addressed, to determine the main objective of this study, which is the role played by Social Workers in evaluating through their intervention the effectiveness of the protection of women's rights in the face of domestic violence in the aforementioned institution. Domestic violence is an issue that generates attention in Ecuador as in all countries in the world, given that, every day you can see and hear news about violence against women or their family circle. This is due to the scope it has had in recent years and because it is a phenomenon in which women and children are the most vulnerable to an action that consists of physical, psychological or sexual abuse carried out by a member of the family. For the execution of the research, a descriptive methodology was used, since it will allow a study to be carried out where it will detail facts and documentary since it is based on data through existing sources and bibliography with a qualitative approach because it is based on describing and carrying out a thorough analysis of the professional intervention of the Social Worker. this will allow us to know the importance of their work in the field of protection in the face of this situation of vulnerability of rights that challenges society, in order to achieve the objectives such as knowing the protection actions, strategies implemented by the Department of Social Work in the Judicial Unit for the protection of women's rights and analyzing the results of said intervention within the institution, through techniques such as direct observation to evidence the reality of the Social Worker in the judicial unit of violence against women and family, documentary analysis that will allow information to be collected, and the interview that allows synthesizing the information that is required to obtain adequate results through the questions used. Therefore, as it is a current problem, it needs to be addressed in order to take intervention actions in families, where an insecure scenario is reflected, which demands help and external support for the organization of family relationships, since intra-family violence is accompanied by a series of abusive episodes by one of the members of the family nucleus towards the other. with the aim of causing physical or emotional damage that generates negative impacts and effects that leave sequelae throughout their lives. Once the research techniques were implemented to know the actions of the professionals and the satisfaction of the care provided to the users of the institution, the results were obtained where revictimization is evidenced during the care in the first instance, therefore, it is important to apply improvements to the care protocol using a multidisciplinary interview that reduces revictimization, guaranteeing that victims receive respectful treatment, empathetic and fair, during the interview with the technical team in order to provide a safe environment throughout the judicial process.
La investigación responde a la vulneración que tienen las mujeres en sus derechos a causa de la violencia intrafamiliar con la evidencia en casos registrados en la Unidad Judicial de Violencia contra la Mujer y la Familia en la ciudad de Machala y en base a lo abordado determinar el objetivo principal de este estudio que es el papel que desempeña los Trabajadores Sociales al evaluar a través de su intervención la efectividad de la protección de los derechos de las mujeres ante la violencia intrafamiliar en la institución antes mencionada. La violencia intrafamiliar es un tema que produce atención en el Ecuador como en todos los países en el mundo, dado que, todos los días se puede ver y escuchar noticias sobre la violencia contra la mujer o de su círculo familiar. Esto se debe por el alcance que ha tenido en los últimos años y porque es un fenómeno en el que las mujeres y los niños son los más vulnerables a una acción que consiste en maltrato, físico, psicológico o sexual ejecutado por un miembro de la familia. Para la ejecución de la investigación se utilizó una metodología tipo descriptiva, dado que permitirá realizar un estudio donde detallará hechos y documental ya que se basa en datos por medio de fuentes existentes y bibliográficas con enfoque cualitativo porque se basa en describir y realizar un análisis minucioso de la intervención profesional del Trabajador Social, esto permitirá conocer la importancia de su labor en el ámbito de protección ante esta situación de vulnerabilidad de derechos que desafía a la sociedad, con el fin de alcanzar a cumplir con los objetivos como el conocer las acciones de protección, estrategias implementadas por parte del Departamento de Trabajo Social en la Unidad Judicial para la protección de los derechos de las mujeres y analizar los resultados de dicha intervención dentro de la institución, a través de técnicas como la observación directa para evidenciar la realidad del Trabajador Social en la unidad judicial de violencia contra la mujer y familia, el análisis documental que permitirá recopilar información, y la entrevista que permite sintetizar la información que se requiere para obtener resultados adecuados a través de las preguntas empleadas. Por ende, al ser una problemática actual necesita ser abordada para tomar las acciones de intervención en las familias, donde se plasma un escenario inseguro, que demanda de ayuda y soporte externo para la organización de las relaciones familiares, ya que la violencia intrafamiliar va acompañada de una serie de episodios abusivos por uno de los integrantes del núcleo familiar hacia el otro, con el objetivo de causarle daños físicos o emocionales que generan impactos y efectos negativos que dejan secuelas a lo largo de su vida. Una vez implementadas las técnicas de investigación para conocer el accionar de los profesionales y la satisfacción de la atención otorgada a los usuarios de la institución se obtuvo los resultados donde se evidencia la revictimización durante la atención en primera instancia por ello es importante aplicar mejoras al protocolo de atención empleando una entrevista multidisciplinaria que disminuya la revictimización garantizando que las víctimas reciban un trato respetuoso, empático y justo, durante la entrevista con el equipo técnico con el fin de brindar un entorno seguro durante todo el proceso judicial.
Keywords: TRABAJADOR SOCIAL; VIOLENCIA INTRAFAMILIAR; VICTIMA; VULNERACION; PROTECCION